Effect of Artemisia vulgaris Extract on P53 Expression and Caspase-8 Expression (Study on Adenocarcinoma Mammae C3H Mice Given Adriamycin- Cyclophosphamide Chemotherapy Regimen) - Sugiharto, Jonathan; Hardian; Selamat Budijitno (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Background: The incidence of breast cancer worldwide is still high. Surgery remains the top choice with other modalities of chemotherapy. radiation. and immunotherapy such as Artemisia vulgaris (AV). Purpose : The study was aimed to demonstrate that administration of AV extract increased the levels of p53 and Caspase-8 in adenocarcinoma mammae. Methods: This study used